Laparotomy closure palisade - Iacopino, Julio; Czarnevicz, Daniel; Cilleruelo, Roberto; Colet, Andrés (Cirugía del Uruguay, 1991)
The authors present a modification of the closing technique for abdominal wall by means of polyethylene tubes that consists of making them pass on the outside of the sheath of the rectus abdominis muse/es and instead of knotting their ends, securing them by different procedures. In this way a better result is obtained as regards parietal integrity and ventilatory dynamica, and it makes definitive parietal closing easier. The authors emphasize its indication in contained laparotomy patients.